Understanding the relationship between foots characteristics and running shoes among students / Muhammad Al Aiyubbi Adnanni Zulkarnain - Zulkarnain, Muhammad Al Aiyubbi Adnanni (2023)
It has been acknowledged that technology has advanced significantly in recent years, influencing the way items are manufactured, including running shoes. Running shoes firms have created many types of shoes for various types of shoes for various types of people. Due to this situation, customers have been exposed to a wide variety of shoe options in the market. As a result, the problem related to the selection of the type of shoe that is related to the type of character of the foot has occurred indirectly, which has resulted in the problem of mistakenly buying shoes. The goal of this research is to find out how students’ feet affect the type of running shoes with examine their foot characteristics and the type of running shoes that are available in the market and assist students in selecting the best running shoes for their feet. 61 students Universiti Teknologi MARA Melaka (Kampus Alor Gajah) were randomly selected to participate in this study. The study employed a survey design that involved the demographics data, running experience, buying experience and awareness knowledge.